MULTIDIMENSIONAL CHALLENGES OF THE AGRICULTURAL SECTOR AT NATIONAL AND GLOBAL LEVELS - Karimah, Rafifah; Afifah, Munafatin; Ibnu, Muhammad (Lampung University, 2025)
The diverse challenges faced by the agricultural sector make prioritization crucial. This approach allows stakeholders to focus on the most urgent and critical issues first before addressing lower priority ones. This study aims to analyze the main (priorities) challenges for the agricultural sector, both nationally and globally. This study employed a qualitative approach through a literature review of 100 studies published over the past 10 years (2013-2023). The findings identify 8 (eight) major challenges in the agricultural sector, namely climate change and risks of water deficits, energy, biodiversity and ecosystem services, social infrastructure, governance and policies, food supply chains, consumption patterns, and intensification of sustainable agriculture. This study concludes that achieving sustainable agriculture and food systems necessitates a robust and balanced understanding of both agronomy and ecology, enhancement of social capital through farmer and community participation, and policies that prioritize environmental preservation and human welfare while remaining unaffected by the political interests of a few parties.